Variació històrica. Els temps en la variació lingüística - Moran i Ocerinjauregui, Josep (Caplletra. Revista Internacional de Filologia, 1998)
This paper comments and reflects upon the inherent nature of time during any linguistic realization, and therefore during variation.This happens aside from the abstractions made by a sincronicity due to the descriptive methodology used or due to the theoreticalpremises that propose a sincronicity.